'Be kind to yourself – because you're doing fine': using self-determination theory to explore the health-related experiences of primiparous women participating in a co-active life coaching intervention. Issue 1 (2nd January 2020) - Harvey, J.; Pearson, E. S.; Mantler, T.; Gotwals, J. K.
ABSTRACT: The postpartum period is a vulnerable time for the onset of excess weight, especially in primiparous (first-time) mothers. Co-Active Life Coaching (CALC) is a cognitive behavioural technique that has shown utility for enhancing health in populations with obesity. While the Co-Active model has been grounded in Self-Determination Theory (SDT), no empirical studies have investigated CALC as it relates to the fulfilment of SDT's basic psychological needs (autonomy, competence, and relatedness). Using this theoretical lens, the purpose of this study was to explore qualitatively the experiences of primiparous women participating in a telephone-based CALC intervention. Nine first-time mothers engaged in eight-weekly sessions delivered by Certified Professional Co-Active Coaches. Semi-structured interviews were conducted following the intervention and analyzed using deductive thematic content analysis. Several detractors from (e.g., motherhood-specific challenges) and supporters of (e.g., being kind to oneself) SDT's basic psychological needs were discussed in the context of health behaviour change. The coaching relationship and delivery mode were deemed especially helpful (e.g., providing a need-supportive environment, facilitating accountability). When provided by telephone, this coaching style may be a useful health promotion tool for primiparous mothers: a population with unpredictable schedules and multifaceted responsibilities. A larger sample size with a longer follow-up period is now recommended.